Pathological Studies and Postmortem Computed Tomography of Dolphins with Meningoencephalomyelitis and Osteoarthritis Caused by Brucella ceti - Granados-Zapata, Andrés (2022)
We thank all the personnel of the Aquatic Animal Virtopsy Lab, Hong Kong and SENASA of Costa Rica, especially to the Central Pacific Region and LANASEVE, Hellen Porras Fernández, Juan Carlos Alvarado, Osvaldo Barrantes Granados, Jacqueline Cubillo Morera, Josimar Estrella Morales, Eunice Viquez Ruiz, and the personnel from Parque Marino del Pacífico for their collaboration with the localization and handling of the stranded animals. Additionally, we want to give a special thanks to Jimmy Vargas Olivares from the Hospital San Vicente de Paul for assisting in the histopathological preparations. We also thank the Municipal Police and Coastguard of Costa Rica, the personnel from the Program of Investigation of Tropical Diseases (PIET) to Nazareth Ruiz Oceans 2022, 3 202 Villalobos, and Karol Roca for their collaboration during necropsies. This work was supported and approved as part of the National Program of Wildlife of SENASA San José, Costa Rica.